Multi-GNSS Data Processing and Analysis in Point Positioning for Brazilian Stations in Months of High and Low Ionospheric Activity - Souza, Felipe Tintino Linhares de (2025)
The Global Navigation Satellite Systems (GNSS) have been increasingly used in positioning-related activities. The term GNSS includes the U.S. Global Positioning System (GPS), the Russian GLObal’naya NAvigationnaya Sputnikowaya Sistema (GLONASS), initially developed by the Soviet Union, the European Union’s Galileo, the Chinese BeiDou, and Satellite and Ground Based Augmentation System (SBAS and GBAS). With the large number of satellites available, the trend today is to combine the systems at the user level, improving availability and positioning accuracy. The objective of this study is to process and analyze GNSS data from Brazilian monitoring stations using point positioning (PP), correlating with the ionosphere activity and the multipath around each station. Four systems were considered individually and combined, under different atmospheric conditions. The results were evaluated in terms of the Root Mean Square Error (RMSE), considering the horizontal and vertical bias, as well as the respective uncertainties, given by the Least Squares Method (LSM). The multi-GNSS positioning presented the best results, mainly due to the redundancy in the number of observations (average of 29 satellites per epoch), with a root-mean-square error of 1.5 m. GPS and Galileo showed the best performance among the individual results.